Reading Materials for Individual Learning: Sources and Challenges Saadillah, Muhamad Aji Pangestu, Fajrianor - Saadillah; Muhamad Aji Pangestu; Fajrianor (ELITE Association Indonesia, 2023)
This study described about the source of reading material that students use for individual learning in English class and also their challenges on reading. Source of reading materials include teaching material, both written and unwritten, or all types of materials used to teachers in carrying out teaching and learning activities. The design of this research using descriptive qualitative. The participants in this research included 26 students from twelfth grade at MAN Tanah Laut. On collecting data, the researcher used observation and interview. The data were analyze based on descriptive qualitative approach. Based on the result of the research it could be concluded that source of reading material that students used for individual learning in English class from school program and also provide the link to support teaching and learning activity. The challenges that students face when comprehending the source of reading materials for individual learning in English class such as lack of vocabularies, grammatical error, not understand meaning, and difficult to translate every new word. Keywords: Reading Material, Individual Learning, Sources, Challenges